A parameter less stochastic optimization technique for tuning of speed PI controller of DTC induction motor drive - Naveen Goel; Saji Chacko; R. N. Patel (IAES International Journal of Robotics and Automation (IJRA), 2019)
The Direct Torque Controlled (DTC) induction motor (IM) drives over the years have been the work force of industries. The popularity of this motor drive is due to the low cost and low maintenance of induction motor coupled with the fast dynamic response and simple control structure of direct torque control method. The robust performance of the DTC induction motor drive depends on the proper tuning of its speed controller. The proposed paper make use of the stochastic optimization technique namely the popular Harmony Search Algorithm and is compared with the parameter free Jaya Algorithm for tuning the gains of the speed proportional integral controller. Simulation studies in MATLAB/Simulink shows the success of the Jaya Optimization for improving the performance of DTC drive with respect to speed and torque peak over shoot and steady state error under different drive operating conditions.